Bedaquiline plus delamanid for XDR tuberculosis - Lachâtre, Marie; Rioux, Christophe; Dû, Damien Le; Fréchet-Jachym, Mathilde; Veziris, Nicolas; Bouvet, Elisabeth; Yazdanpanah, Yazdan (The Lancet infectious diseases, 2016)
The combination was initiated in a patient in whom an effective treatment cannot be designed, in the consideration that its potential life-saving benefits outweigh its unknown adverse event risks; in a department in which more than 100 tuberculosis cases a year are admitted to hospital, of which 14 cases are multidrug-resistant or XDR disease; after a multisciplinary consultation at the national level; and after patient's informed consent. Conditions for this combination use described by Alberto Matteelli and colleagues2 were therefore fulfilled. [...]this combination was initiated under close cardiac monitoring and was well tolerated over a 6 month period.